2022
DOI: 10.1063/5.0083081
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear regimes of the electron cyclotron drift instability in Vlasov simulations

Abstract: We report on a novel investigation of the nonlinear regime of the electron cyclotron drift instability using a grid-based Vlasov simulation. It is shown that the instability occurs as a series of cyclotron resonances with the electron beam mode due to the E × B drift. In the nonlinear regime, we observe condensation of fluctuations energy toward the lowest resonance mode and below, i.e., an inverse energy cascade. It is shown that the characteristics of the nonlinear saturation state remain far from the ion-so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…In practice, quantifying these effects requires an understanding of the growth rate-the rate at which the EDI extracts momentum from the background plasmaand the power spectrum-the distribution of energy in the waves as a function of frequency and lengthscale [14]. While there are many theories for these aspects of the EDI [4,[15][16][17][18][19], there has yet to be a direct experimental measurement of the linear growth and nonlinear wave coupling processes that govern the EDI spectrum. This lack of experimental data speaks to a broader problem commonly encountered in measuring wave dynamics in low temperature plasmas [5]: established methods based on length-scale bispectral analysis [20,21], developed for higher energy density plasmas, do not translate well to space-based and low temperature systems.…”
mentioning
confidence: 99%
“…In practice, quantifying these effects requires an understanding of the growth rate-the rate at which the EDI extracts momentum from the background plasmaand the power spectrum-the distribution of energy in the waves as a function of frequency and lengthscale [14]. While there are many theories for these aspects of the EDI [4,[15][16][17][18][19], there has yet to be a direct experimental measurement of the linear growth and nonlinear wave coupling processes that govern the EDI spectrum. This lack of experimental data speaks to a broader problem commonly encountered in measuring wave dynamics in low temperature plasmas [5]: established methods based on length-scale bispectral analysis [20,21], developed for higher energy density plasmas, do not translate well to space-based and low temperature systems.…”
mentioning
confidence: 99%
“…It is clear that EDI shows different characteristics in each growth stage due to different excitation mechanisms. Tavassoli et al [22] showed that in numerical simulation studies of EDI, numerical noise often significantly affects the simulation results and obscures the actual growth mechanisms at each stage. Asadi et al [23] showed that increasing the number of macro-particles in the model can eliminate the numerical noise to some extent.…”
Section: Introductionmentioning
confidence: 99%